L’ingénieur et sa responsabilité professionnelle - Arsenault, Laurent (Assurances)

(untitled) (HEC Montréal, 1990)
The increased number and size of claims and lawsuits against all professionals have not spared engineers at a time when, despite a vigorous economy, profit margins appear to have remained modest. This article presents a brief summary of the legal principles underlying the professional liability of engineers and how they are applied in real life cases in court judgements. The extent of the engineer's liability will be shown in situations which did not appear dangerous at first. In many cases, practicing engineers will find themselves involved in litigious situations more or less by surprise and without any experience in the adequate management of the real risks to which they are exposed. Certain problem-prone attitudes and behaviours are to be avoided. The following article provides suggestions on how to minimize the risks even in very unfavorable circumstances.